Congestion control of Wavelet image compression over wireless networks - Tuy, Ho Anh; An, Nguyen Vinh (VNU Journal of Science: Mathematics - Physics; Vol 23 No 1, 2007)
The demand of transmission of images and video is increasing quickly recently and researchers arc trying to invest good solutions to improve thc quality of thesc over wireless networks. There are sỉill challengcs due to the đifferent characteristics and quality of images betwecn wired and wireless channels. An important issue is congestion control to cnsure network siability and achieve a rcasonably fair distribution of the network resources among the users. The paper will prescnt a model of congcstion control by combining Wavelet image compression at the source vvith applying Fuzzy logic technique to control traíĩics. The simulation shovvs a good result, t h e transmission rate can be adjusted to adapt the changes of \vireless channel, the buffer of intcrmcđiate devices vvill not be svvung from idle to ovcrflow or vice versa so that the cell loss rate is small.